GIS Based hydrologic modelling for infiltration excess overland flow - Mohamad Yusoff, Izham; Abdul Rahman, Alias; Katimon, Ayob (2007)
Rapid population growth, constructions, urbanization, and industrialization have increased impervious area causing hazardous impact towards rate of stormwater infiltrated into soil. Thus the surface overland flow in a post-development area becomes greater than the pre-development area. Concepts of infiltration mechanism need to be reviewed in order to sustain the existing environmental condition. This study aims to determine areas and volume of overland flow generated from Infiltration Excess Overland Flow (IEOF) process by comparing the empirical Horton equation and physically based Green-Ampt equation with the visualisation of spatially based Geographic Information System (GIS) hydrologic modelling. Both equations are analysed by stressing on spatial data handling techniques of map projections and scales. This study is carried out at Sungai Pinang basin, located in North East coast of Penang Island, Malaysia. The areas and volume of IEOF are determined and compared with two different map projections; the Rectified Skew Orthomophic (RSO) and Cassini-Soldner projections with the map scale of 1 : 25 000. Digital layers of Sungai Pinang basin are developed using Autodesk Map 2004 software, while GIS based hydrologic modelling to determine areas and volumes of IEOF are performed using Avenue Script and Spatial Analyst extension within ArcView GIS software. Local authorities could find the results are useful to evaluate the effectiveness of flood management control, sustainability for long-term development purposes, stream restoration, rehabilitation and relocation of construction projects.